Local brassinosteroid biosynthesis enables optimal root growth - Vukašinović, Nemanja; Wang, Yaowei; Vanhoutte, Isabelle; Fendrych, Matyáš; Guo, Boyu; Kvasnica, Miroslav; Jiroutová, Petra; Oklestkova, Jana; Strnad, Miroslav; Russinova, Eugenia (Nature plants, 2021)
Brassinosteroid (BR) hormones are indispensable for root growth and control both cell division and cell elongation through the establishment of an increasing signalling gradient along the longitudinal root axis. Because of their limited mobility, the importance of BR distribution in achieving a signalling maximum is largely overlooked. Expression pattern analysis of all known BR biosynthetic enzymes revealed that not all cells in the Arabidopsis thaliana root possess full biosynthetic machinery, and that completion of biosynthesis relies on cell-to-cell movement of hormone precursors. We demonstrate that BR biosynthesis is largely restricted to the root elongation zone, where it overlaps with BR signalling maxima. Moreover, optimal root growth requires hormone concentrations to be low in the meristem and high in the root elongation zone, attributable to increased biosynthesis. Our finding that spatiotemporal regulation of hormone synthesis results in local hormone accumulation provides a paradigm for hormone-driven organ growth in the absence of long-distance hormone transport in plants.
Keywords: regulace genové exprese u rostlin; Brassinosteroids; kořeny rostlin; Plant Roots; brassinosteroidy; Meristem; regulátory růstu rostlin; Plant Growth Regulators; meristém; Gene Expression Regulation, Plant; Metabolic Networks and Pathways; Arabidopsis; metabolické sítě a dráhy